A Model for Forecasting Dependent Demand in Inventory Replenishment Processes - Ismail Civelek (International Journal of Supply Chain Management, 2015)
We study a capacitated multi-period, multi-product inventory problem under a finite horizon. Our main goal is to understand the impacts of evolution of forecasts for demand streams for multiple products on inventory replenishment decisions. We provide an input modelling technique to model such complex inventory management problem and offer research questions for future investigations. Our main contribution is analysing a complex but very practical problem in inventory management for multiple products and multi-periods when demand streams are dependent of each other and forecasting the demand requires simulation and updating over the finite planning period.